The Economist. (London : Economist newspaper ltd.)
The Economist is a British publication that describes itself as a weekly newspaper. It is mostly written and edited in Britain, focusing on current affairs, international business, politics, technology, and culture. Based in London, the newspaper is owned by the Economist Group, with its core editorial offices in the United States, as well as across major cities in continental Europe, Asia, and the Middle East. The newspaper has a prominent focus on data journalism and interpretive analysis over original reporting, to both criticism and acclaim.
Keywords: Business, Economy and Management; General and Others; Informatieve tijdschriften